Edukasi Kesehatan Gigi dan Mulut di Masa Pandemi Covid 19 - Widyastuti, Nugraheni; Nur Aida, Wanda; Supriatna, Agus (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2023)
Dental and oral health problems in Indonesia have increased based on the results of Riskesdas in 2013 by 25.9%, South Sulawesi Province by 36.2%, while in 2018 there was an increase in damaged/cavities/sick teeth in Indonesia to 45.3% and in South Sulawesi Province as much as 55.5%. In Makassar City it was 52.09% and at the age of 35 – 44 years it was 61.01%. These dental and oral health problems certainly require treatment at a health facility to receive comprehensive medical treatment. However, the Covid-19 pandemic situation also had an impact after disrupting people's access to health services. Therefore, promotive actions are very important at this time to prevent dental and oral health problems, one of which is education by maintaining dental and oral hygiene effectively. This research aims to find out how to maintain healthy teeth and mouth during the Covid-19 pandemic and empower people to be able to independently carry out Covid-19 health protocols in every activity. This research method uses quasi-experimental with one group pretest-posttest design. The research stage is measuring the level of knowledge of residents before and after education is carried out. Data were tested using anova, Shapiro Wilk, and Wilcoxon test. The results of the paired data effectiveness test show that the p-value is 0.000 (p <0.05), meaning there is an increase in knowledge. The conclusion is that there has been an increase in knowledge among the people of Banta-Bantaeng Village with dental and oral health education during the Covid-19 pandemic.